Beyond the Bayley: Neurocognitive Assessments of Development During Infancy and Toddlerhood. Issue 2 (17th February 2019) - Brito, Natalie H.; Fifer, William P.; Amso, Dima; Barr, Rachel; Bell, Martha Ann; Calkins, Susan; Flynn, Albert; Montgomery-Downs, Hawley E.; Oakes, Lisa M.; Richards, John E.; Samuelson, Larissa M.; Colombo, John
ABSTRACT: The use of global, standardized instruments is conventional among clinicians and researchers interested in assessing neurocognitive development. Exclusively relying on these tests for evaluating effects may underestimate or miss specific effects on early cognition. The goal of this review is to identify alternative measures for possible inclusion in future clinical trials and interventions evaluating early neurocognitive development. The domains included for consideration are attention, memory, executive function, language, and socioemotional development. Although domain-based tests are limited, as psychometric properties have not yet been well-established, this review includes tasks and paradigms that have been reliably used across various developmental psychology laboratories.